The role of retinal Müller cells in diabetic retinopathy and related therapeutic advances - Yang, Shuo; Qi, Shounan; Wang, Chenguang (Frontiers in Cell and Developmental Biology, 2022)
Diabetic retinopathy (DR) is a significant complication of diabetes. During the pathogenesis of retinal microangiopathy and neuronopathy, activated retinal Müller cells (RMCs) undergo morphological and structural changes such as increased expression of glial fibrillary acidic protein, disturbance of potassium and water transport regulation, and onset of production of a large number of inflammatory and vascular growth factors as well as chemokines. Evidently, activated RMCs are necessary for the pathogenesis of DR; therefore, exploring the role of RMCs in DR may provide a new target for the treatment thereof. This article reviews the mechanism of RMCs involvement in DR and the progress in related treatments.